Diagnostic Performance of Infrared Thermography, Quantitative Sudomotor Axonal Reflex Testing, and 3-Phase Bone Scintigraphy for Complex Regional Pain Syndrome Diagnosis: A Retrospective Observational Study - Noh C; Lee J; Choi HY; Park E; Shin YS; Hong B; Ko Y; Oh C; Lee SY (Journal of Pain Research)
Chan Noh,1,2,* Jiyong Lee,1,2,* Hye Young Choi,1 Eunhye Park,1 Yong Sup Shin,1,2 Boohwi Hong,1,2 Youngkwon Ko,1,2 Chahyun Oh,1,2 Sun Yeul Lee1,2 1Department of Anesthesiology and Pain Medicine, Chungnam National University Hospital, Daejeon, Korea; 2Department of Anesthesiology and Pain Medicine, College of Medicine, Chungnam National University, Daejeon, Korea*These authors contributed equally to this workCorrespondence: Sun Yeul Lee; Chahyun Oh, Email neoquack@gmail.com; ohchahyun@gmail.comPurpose: Complex regional pain syndrome (CRPS) diagnosis poses challenges due to the absence of an objective and definitive test. Although laboratory tests such as infrared thermography, quantitative sudomotor axonal reflex testing (QSART), and 3-phase bone scintigraphy have been considered diagnostic aids, their use remains controversial. This retrospective study aimed to elucidate the diagnostic validity and potential value of these modalities for the diagnosis of CRPS.Patients and Methods: The Budapest criteria were used to diagnose CRPS, and infrared thermography, QSART, and 3-phase bone scintigraphy were performed as ancillary tests. Diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis and measurement of sensitivity, specificity, and positive and negative likelihood ratios.Results: Of the 41 patients assessed, 26 (63.4%) were diagnosed with CRPS based on these criteria. Among the three tests, only infrared thermography demonstrated significant diagnostic performance (area under the ROC curve, 0.718; 95% confidence interval, 0.569– 0.866; p = 0.003). Infrared thermography revealed a positive and negative likelihood ratio of 2.308 and 0.346, respectively, indicating clinically informative results. The three positive results exhibited the highest specificity (0.933) and positive predictive value (0.917).Conclusion: Among the three laboratory tests for CRPS, infrared thermography was the most useful. QSART and 3-phase bone scintigraphy did not show a significant diagnostic performance; however, combining the results of all three tests may provide additional diagnostic confidence in certain cases.Keywords: complex regional pain syndrome, infrared thermography, quantitative sudomotor axonal reflex testing, 3-phase bone scintigraphy